Edukasi Pencegahan dan Penanganan Kekerasan Seksual Terhadap Organisasi Kemahasiswaan di Kota Mataram, Nusa Tenggara Barat - Nur Adhi, Rakhmat; Firmansyah, Agung; Rosyidah, Feryna Nur; Utomo, Jepri (Universitas Madako Tolitoli, 2025)
Sexual violence in higher education institutions has become a critical concern, particularly in Mataram City, where several cases have been reported in recent years. Unequal power relations within academic settings often position students, especially women, as vulnerable targets of such violence. In response to this issue, a community service team organized an educational program on Prevention and Handling of Sexual Violence, targeting members and leaders of student organizations across three universities in Mataram. The program was conducted on March 3, 4, and 6, 2025, involving a total of 203 participants. The intervention was implemented in three stages. The first stage involved conducting a pre-test and initial observation, which revealed a generally low level of awareness and knowledge among participants regarding sexual violence. The second stage comprised educational sessions designed based on the pre-test results, including both direct instruction and the dissemination of posters containing QR codes that provided access to educational materials and regulatory documents. The final stage involved administering a post-test to evaluate knowledge improvement and awareness development. The evaluation results demonstrated a significant increase in participants' understanding of sexual violence issues and their awareness of the importance of active involvement in prevention and response efforts. This activity contributed meaningfully to fostering a campus culture that is safe, just, and free from sexual violence.